Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.3389/fpls.2017.00066
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Prediction and Evolution Analysis of Arabinogalactan Proteins in the Plant Kingdom

Abstract: Arabinogalactan proteins (AGPs) are a family of extracellular glycoproteins implicated in plant growth and development. With a rapid growth in the number of genomes sequenced in many plant species, the family members of AGPs can now be predicted to facilitate functional investigation. Building upon previous advances in identifying Arabidopsis AGPs, an integrated strategy of systematical AGP screening for “classical” and “chimeric” family members is proposed in this study. A Python script named Finding-AGP is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 69 publications
0
86
0
Order By: Relevance
“…Finally, the reason for the wide range in classical AGP structure includes the complex glycosylation of its protein core. Clearly the tiny minority of AGPs characterized biochemically only hints at their true diversity and versatility emphasized by recent bioinformatics that show higher plants have heavily invested in AGPs (Ma et al ., ). Thus, diverse stimuli might generate specific Ca 2+ signatures (Rudd & Franklin‐Tong, ) based on the distribution, size and composition of AGP glycomodules.…”
Section: Future Research Pathways Guided By Occam and Darwinmentioning
confidence: 97%
“…Finally, the reason for the wide range in classical AGP structure includes the complex glycosylation of its protein core. Clearly the tiny minority of AGPs characterized biochemically only hints at their true diversity and versatility emphasized by recent bioinformatics that show higher plants have heavily invested in AGPs (Ma et al ., ). Thus, diverse stimuli might generate specific Ca 2+ signatures (Rudd & Franklin‐Tong, ) based on the distribution, size and composition of AGP glycomodules.…”
Section: Future Research Pathways Guided By Occam and Darwinmentioning
confidence: 97%
“…A study of the hydroxyproline‐rich glycoproteins (HRGP) superfamily in the 1,000 plant transcriptomics data (1KP) showed that GPI anchored AGPs (GPI‐AGPs) can be identified early in land plant lineages, being present in Glaucophyta, Chromista and green algae (Johnson et al ) and were found throughout land plant evolution in all 1KP groups. Evolutionary studies of chimeric AGPs, many of which are predicted to be GPI‐anchored, could also be identified in the genomes of 47 plant species (Ma et al ). In addition, studies of GPI‐LTPs, proposed to function in the synthesis and/or deposition of cutin and cuticular waxes, in the moss Physcomitrella suggest they share similar features and function to GPI‐LTPs found in flowering plants (Edstam and Edqvist ; Edstam et al ).…”
Section: The Plant Gpi‐anchored Proteomementioning
confidence: 99%
“…On the other hand, cytosolic Ca 2+ gradients originate from Ca 2+ stored in a cell surface AGP-Ca 2+ capacitor [ 12 ]. AGPs are essential components of the Hechtian growth oscillator that amplifies the magnitude and direction of stress vectors regulating plant growth [ 6 ]; that explains why plants have heavily invested in AGPs [ 13 ] and why this investment is so highly diversified [ 14 ]. Many AGPs are developmentally regulated and tissue-specific [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%